O exercício da justiça e a prática da religião em Israel - Maia, Maria Isabel de Barros Bezerra Alves (2008)
The Work, here presented analysises the relation between justice s exercise and Religion s practice, in Israel, aiming at demonstrating which can be found out what there is in common about and what is different between these two Institutions. It investigates, examines the notion regarding to justice, Public life and Jewish theology cornerstone, which is expressed, present in all commandments, in the rabbinical literature, in the being Jewish ontological aspect, demanding from man a worthwhile behaviour in all whole life actions and circumstances, situations. In Humanity s History, Justice concept precedes Science of Law idea. The whole Bible is pervaded by, through Justice s reality, put into practice by man and by God: human Justice, Divine justice. Bible teaches that it is, through the revelation regarding to that one we find out one of the most essential aspects of the rapport between God and man. justice in Israel Israel s justice is bound up, tied to God s justice, in its Israel s History concreteness. Either God s One justice either Israel s one, justice is no more identified with a mere, simple Judiciary System in order to rule and to nullify conflict regarding to interests, for Alliance reality inflict, imposes justice s itself, own code to each one of the parts, enveloped in the question, in the pledge. In the biblical context, justice concept implies, evokes sanctity, holiness, adhesion to God; the concept regarding to justice is identified with the perfection that one, Sanctity, holiness; therefore, the perfect one, the holly one is just. Yahweh reveals Him self as Israel s just-King, as just-God At last, finally, this Work presents, points out a Jewish Laws body, assemblage and aims at enlightening the vinculation, the bond between the sacred element and justice